GAMBARAN PENERIMAAN DIRI PADA PEREMPUAN BALI PENGIDAP HIV-AIDS - Putri, Ida Ayu Karina; Tobing, David Hizkia (Jurnal Psikologi Udayana, 2016)
Recent years, development of the epidemic disease of AIDS (Acquired Immune Deficiency Syndrome) has become quite frightening for the people of the world (Zarpatista, 2012). In Indonesia there are currently 75 regencies/cities which have a very high prevalence of HIV-AIDS, among others due to the increasing of transmission from husband to wife (Wardah, 2013). The province of Bali including is one of the six provinces that has status of epidemic HIV-AIDS besides Papua, Riau, Jakarta, Jawa Barat, and Jawa Timur (Suriyani, 2006). In many cases, women infected with HIV from her partner/husband because women did not have power of both socially and economically to protect herself (Nainggolan, 2004). Based on pre eliminary study that conducted by researchers in Yayasan Citra Usadha (YCUI) on the three regencies area program that is Buleleng, Jembrana, and Karangasem, discrimination recognized did occur in some cases of ODHA in Bali especially women. One of the problem in ODHA’s life is not only related to the stigma and discrimination from the around environment, but also with their self condition acceptance (Rasyida, 2008). This situation attracts researcher to find out the self acceptance in Balinese woman who lives with HIV-AIDS. This study use qualitative method with phenomenological approach and 5 Balinese women who lives with HIV-AIDS as the respondents, the data collected with observation and in depth-interview conducted during 7 months. The result shows that there 9 representation of self-acceptance in Balinese woman who lives with HIV-AIDS which are be grateful, optimistic and always trying to do the optimum, have the right and feel equal with others, do not want to treated differently, want to help and sharing with others, self introspection, being closer with God. Keywords: HIV-AIDS, Self-Acceptance, Balinese Woman